M-commerce em mercados emergentes: o efeito da qualidade na lealdade dos consumidores - de Sousa, Eduardo Mesquita; Lopes, Eliane Herrero; Gonzalez, Marcela (Retail Management Review, 2023)
Objective: The main objective in this study is to examine the effect of quality of m-commerce services on customer satisfaction and loyalty. In addition, we aimed to analyze the psychometric properties of the MS-SQ scale (Mobile Shopping Service Quality) in an emerging country, adjusting the instrument for this context. Methodology: We carried out a survey (n=110), analyzing the data through Structural Equation Modeling (SEM). Originality: This study, despite replicating the measurement scale of the perceived quality of mobile services, is the first to test these measures in an emerging country (Brazil). Main Results: The results of this study confirmed the four dimensions of the MS-SQ (efficiency, achievement, responsiveness, and contact), in addition to the effect of the quality of mobile shopping services on consumer satisfaction and loyalty. Theoretical Contributions: This study brings, in the scale translated from English into Portuguese and applied in Brazil, an effective management tool to measure each of the items that compose it, as a direction for understanding consumer loyalty